Experimental investigation of a data-centre cooling system using a new single-phase immersion/liquid technique - Hnayno, Mohamad; Chehade, Ali; Klaba, Henryk; Polidori, Guillaume; Maalouf, Chadi (Case Studies in Thermal Engineering, 2023)
This paper presents an experimental investigation conducted on a new single-phase immersion/liquid-cooling technique developed at the OVHcloud laboratory, combining a direct-to-chip water-cooling system with passive single-immersion cooling technology. The experimental setup tested the impact of three dielectric fluids (S5X, SmartCoolant and ThermaSafe R), the effect of the water circuit configuration, and the server power/profile. Results suggest that the system cooling demand depends on the fluid's viscosity. As the viscosity increased from 4.6 to 9.8 mPa s, the cooling performance decreased by approximately 6%. Moreover, all the IT server profiles were validated at various water inlet temperatures and flow rates. The energy performance of the proposed technique and the liquid-cooling system previously used by OVHcloud was compared at a 600 kW data centre (DC). The proposed technique showed a reduction in the DC electrical power consumption by at least 20.7% compared to the liquid-cooling system. Finally, the cooling performance of the air- and liquid-cooled systems and the proposed solution was compared computationally at the server level. When using the proposed solution, the energy consumed per server was reduced by at least 20% compared with the air-cooling system and 7% compared with liquid-cooling system.
Keywords: Data-centre cooling; Direct-to-chip water cooling; Heat transfer; Liquid cooling; Passive cooling; Single-phase immersion cooling